2021
DOI: 10.1002/aelm.202100551
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Macroscopic Alignment of Chlorobenzo[c]‐[1,2,5]thiadiazole‐Based Semiconducting Copolymers with Controlled Regiochemistry

Abstract: Solution‐processable donor–acceptor‐type conjugated copolymers are considered one of the most promising alternatives to inorganic semiconductors. The introduction of strong electron‐withdrawing groups in the acceptor units of the copolymers has been shown to favor fast charge transport; however, the correlation among the halogen‐substituted molecular structure, solid‐state packing, and charge transport properties is unclear. In this study, new chlorine‐atom‐substituted donor–acceptor copolymers comprising chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…[154] The strategy of self-assembly in nanogrooved substrates was also confirmed by Cho and coworkers. [155] In addition, Teng and coworkers found that highly aligned PCDTPT films can also be obtained by direct spin coating on the nanogrooved substrates when 5% CN is added to the solution. [156] There are many other methods to promote the alignment of D-A conjugated polymer films, such as epitaxial crystallization on oriented polyethylene substrates, .…”
Section: Promoting the Alignment Of Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…[154] The strategy of self-assembly in nanogrooved substrates was also confirmed by Cho and coworkers. [155] In addition, Teng and coworkers found that highly aligned PCDTPT films can also be obtained by direct spin coating on the nanogrooved substrates when 5% CN is added to the solution. [156] There are many other methods to promote the alignment of D-A conjugated polymer films, such as epitaxial crystallization on oriented polyethylene substrates, .…”
Section: Promoting the Alignment Of Filmsmentioning
confidence: 99%
“…[ 154 ] The strategy of self‐assembly in nanogrooved substrates was also confirmed by Cho and coworkers. [ 155 ] In addition, Teng and coworkers found that highly aligned PCDTPT films can also be obtained by direct spin coating on the nanogrooved substrates when 5% CN is added to the solution. [ 156 ]…”
Section: Regulation Of the Aggregated Structure Of Semi‐crystalline D...mentioning
confidence: 99%
“…[7,8] In state-of-the-art OFETs, high hole and electron carrier mobilities surpassing 14 and 7 cm 2 V -1 s -1 , respectively, have been achieved using D-A type polymers synthesized by alternative copolymerization of D moieties, such as oligothiophenes, and A moieties, such as isodingo, naphthalenedicarboximide, and diketopyrrolopyrrole constitutes. [9][10][11][12][13][14][15][16][17] However, the benchmark poly(3hexylthiophene) (P3HT) polymer has been one of the most experimented conjugated polymers for organic electronic devices. [18][19][20][21] This is because of the strong self-assembling ability in both solution and solid state, which contributes to an enhanced charge carrier mobility by forming a highly ordered state of polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…Electrons are delocalized along the CP chains, resulting in electrical conductivity and unique optical properties. 20−22 Additionally, CPs are characterized by solubilizing side chains, which increase their solubility in various organic solvents, 23 enabling thin-film preparation via various solution-processing techniques, such as spin coating, 24 bar coating, 25 capillary force-induced casting, 26 and inkjet printing. 27 In most cases, CP thin films exhibit semicrystalline characteristics, indicating a mixture of crystalline and amorphous domains.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this way, significant advancements in these fields have been achieved, especially in the development of CP materials with rubber-like elongation properties, namely stretchable organic semiconductors. , CPs are commonly characterized by alternating C–C single and C=C double bonds in their backbone, forming a conjugated π-electron system. Electrons are delocalized along the CP chains, resulting in electrical conductivity and unique optical properties. Additionally, CPs are characterized by solubilizing side chains, which increase their solubility in various organic solvents, enabling thin-film preparation via various solution-processing techniques, such as spin coating, bar coating, capillary force-induced casting, and inkjet printing …”
Section: Introductionmentioning
confidence: 99%